2015
DOI: 10.2308/accr-51053
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Comparability and the Accuracy of Peer-Based Valuation Models

Abstract: We examine the link between enhanced accounting comparability and the valuation performance of pricing multiples. Using the warranted multiple method proposed by Bhojraj and Lee (2002, Journal of Accounting Research) and controlling for economic comparability, we demonstrate how enhanced accounting comparability leads to better peer-based valuation performance.Empirical tests using firms from 15 EU countries over the period 1997-2011 (with comparable peers selected from the entire cross-section of foreign f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…) for investors (such as shareholders and creditors) and specialized monitors (such as financial analysts and auditors) . Therefore, investors and specialized monitors are better able to evaluate the company's performance (i.e., lower estimation risk), as peer‐based comparability helps improve the valuation accuracy of analyzing the business fundamentals of the company (Young and Zeng ; Sohn ).…”
Section: Introductionmentioning
confidence: 99%
“…) for investors (such as shareholders and creditors) and specialized monitors (such as financial analysts and auditors) . Therefore, investors and specialized monitors are better able to evaluate the company's performance (i.e., lower estimation risk), as peer‐based comparability helps improve the valuation accuracy of analyzing the business fundamentals of the company (Young and Zeng ; Sohn ).…”
Section: Introductionmentioning
confidence: 99%
“…Groups of different industries will give different risk levels, so the industry group can be a good comparison group [26]. The accuracy of the comparison group selection will improve the valuation accuracy [27]. Valuation by industry combined with growth (ROE) gives the best results compared with the industry and market, and industry combined with the size of the companies [12].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…They concluded that a specific industry could not provide enough criteria, and other control factors like size, profitability and risk have to be added (Alford, 1992;Kim & Ritter, 1999;Bhojraj & Lee, 2002; E. Lie & H. J. Lie, 2002;Liu, Nissim, & Thomas, 2002López, Antón, & Cerviño, 2011;Young & Zeng, 2015;Celli, 2017;Rubio, 2019).…”
Section: Introductionmentioning
confidence: 99%